Composite particles, cathodes and solid-state batteries
Coating positive electrode active material particles with a phosphoric acid compound in all-solid-state batteries addresses thermal instability issues, enhancing thermal stability and safety by suppressing heat generation and sulfide gas production.
Patent Information
- Application Number
- JP2022062359
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-04-04
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2042-04-04
AI Technical Summary
Existing all-solid-state batteries face issues with insufficient thermal stability of the positive electrode active material layer, leading to increased heat generation and reduced battery capacity due to direct contact between the solid electrolyte and positive electrode material, which can accelerate deterioration.
The use of composite particles comprising positive electrode active material particles coated with a phosphoric acid compound coating film, where the coating film contains a specific mass fraction of phosphorus and thickness, and a controlled lithium concentration, to inhibit oxygen reaction and suppress heat generation.
The composite particles effectively reduce heat generation and enhance thermal stability, thereby improving the safety and performance of all-solid-state batteries by minimizing sulfide gas production and maintaining battery capacity.
Smart Images

Figure 0007613407000002 
Figure 0007613407000003 
Figure 0007613407000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composite particle, a positive electrode, an all-solid-state battery, and a method for producing the composite particle. [Background technology]
[0002] Patent Document 1 (JP 2010-135090 A) discloses a positive electrode active material formed by a gas phase method and equipped with a reaction suppressor made of a polyanion structure-containing compound containing lithium, and an all-solid-state battery including the positive electrode active material. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2010-135090 A Summary of the Invention [Problem to be solved by the invention]
[0004] It has been proposed to form a coating film on the surface of positive electrode active material particles. For example, in the all-solid-state battery described in Patent Document 1, the coating film prevents direct contact between the solid electrolyte and the positive electrode active material particles, thereby reducing resistance.
[0005] On the other hand, in the technology described in Patent Document 1, the thermal stability of the positive electrode active material layer is insufficient, that is, it is considered that the amount of heat generated from the electrode is large. In such a case, deterioration of the electrode is accelerated, and the battery capacity is reduced.
[0006] Therefore, an object of the present disclosure is to improve the thermal stability of a positive electrode active material layer. [Means for solving the problem]
[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.
[0008] [1] The composite particle includes a positive electrode active material particle and a coating film. The positive electrode active material particle includes a lithium-containing composite oxide having a layered rock salt structure. The coating film covers at least a part of the surface of the positive electrode active material particle. The coating film includes a phosphate compound.
[0009] The composite particles satisfy the relationship of the following formula (1).
[0010] X P / T≧0.04 (1) In the above formula (1), X P indicates the mass fraction of phosphorus (P) contained in the composite particles measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES). T indicates the film thickness of the coating film measured by a scanning electron microscope (SEM).
[0011] All-solid-state batteries are known to be less susceptible to fire because they do not use organic electrolytes, but sulfide all-solid-state batteries have the risk of generating sulfide gas when the sulfide solid electrolyte reacts with oxygen from the positive electrode material.
[0012] Phosphate compounds including lithium phosphate are widely known as flame retardants. The phosphate compounds have also been used in conventional lithium ion batteries to suppress heat generation in the event of an abnormality. It is believed that by coating the surface of the positive electrode active material particles with the phosphate compound, it is possible to suppress, for example, the reaction of oxygen released by an overcharged positive electrode at high temperature with phosphoric acid to generate sulfide gas.
[0013] The inventors have found that the higher the concentration of phosphoric acid in the composite particles, the more the amount of heat generated from the electrode can be reduced. In other words, the higher the amount of P per unit thickness of the coating film, the more the heat generated by oxygen from the positive electrode material can be suppressed.
[0014] [2] The composite particles may satisfy the relationship of the following formula (2).
[0015] C Li / C P <=2.5 (2) In the above formula (2), C Li indicates the elemental concentration of lithium (Li) determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy. P indicates the elemental concentration of P determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy.
[0016] [3] The composite particles may have a coverage of, for example, 80% or more. The coverage is measured by X-ray Photoelectron Spectroscopy (XPS).
[0017] [4] The positive electrode includes the composite particles described in [1] above and a sulfide solid electrolyte.
[0018] [5] The all-solid-state battery includes the positive electrode described in [4] above.
[0019] [6] A method for producing composite particles includes the following (a) and (b):
[0020] (a) A mixture is prepared by mixing a coating liquid with positive electrode active material particles.
[0021] (b) drying the mixture to produce composite particles.
[0022] The coating liquid includes a solute and a solvent.
[0023] The coating liquid adhered to the surface of the positive electrode active material particles is dried to form a coating film. The coating liquid described in [6] above can form the coating film described in [1] above.
[0024] [7] The solute may include, for example, a phosphate compound.
[0025] The coating liquid may satisfy, for example, the relationship of the following formula (3).
[0026] 0≦n Li / n P <= 1.5 (3) In the above formula (3), n Li indicates the molar concentration of lithium in the coating solution. P indicates the molar concentration of phosphorus in the coating solution.
[0027] [8] (b) above may include forming composite particles, for example by spray drying. [Brief description of the drawings]
[0028] [Figure 1] FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing the all-solid-state battery in this embodiment. [Diagram 3] FIG. 3 is a schematic flow chart of the method for producing composite particles in this embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure.
[0030] <Definitions of terms, etc.> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.
[0031] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."
[0032] Elements expressed in the singular form include the plural form unless otherwise specified. For example, a "particle" can mean not only a single particle, but also an aggregate of particles (powder, powder, particle group).
[0033] Unless otherwise specified, the order of execution of the steps, operations, and the like included in various methods is not limited to the order described. For example, the steps may proceed simultaneously. For example, the steps may be performed before or after each other.
[0034] For example, a numerical range such as "m to n%" includes the upper limit and the lower limit unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper limit or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.
[0035] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may be allowed.
[0036] "D50" refers to the particle size at which the cumulative frequency from the small particle size side reaches 50% in the volume-based particle size distribution. D50 can be measured by a laser diffraction method. For example, a laser diffraction type particle size distribution measuring device "Product name SALD-7500" (or an equivalent product) manufactured by Shimadzu Corporation may be used.
[0037] <XPS Measurement> (composition ratio of particle surface) C in the above formula (2) Li , C P can be measured by the following procedure. An XPS instrument is prepared. For example, an XPS instrument manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS instrument. Narrow scan analysis is performed with a pass energy of 224 eV. The measurement data is processed by analysis software. For example, an analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The peak area (integral value) of the Li1s spectrum is used to determine the elemental concentration of Li (C Li ) The peak area of the P2p spectrum is converted to the elemental concentration of P (C P ) is converted to C Li C P By dividing by Li / C P ) is obtained.
[0038] (Coverage rate) The coverage is also measured by XPS. By analyzing the above measurement data, the ratio of each element can be obtained from the peak areas of C1s, O1s, P2p, and M2p3.
[0039] The coverage rate is calculated by the following formula (4).
[0040] θ=P / (P+M)×100 (4) In the above formula (4), θ represents the coverage (%), and P and M represent the ratio of each element.
[0041] Note that "M2p3" and M in the above formula (4) are constituent elements of the positive electrode active material particles and represent an element other than Li and oxygen (O). That is, the positive electrode active material particles may be represented by the following formula (5).
[0042] LiMO2(5) M may be composed of one element or multiple elements. M may be, for example, at least one element selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn) and aluminum (Al). When M contains multiple elements, the sum of the composition ratios of the elements may be 1.
[0043] For example, the positive electrode active material particles are "LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2”, the above formula (4) can be transformed into the following formula (4'):
[0044] θ=P / (P+Ni+Co+Mn)×100 (4') In the above formula (4'), Ni represents the element ratio of Ni determined from the peak area of Ni2p3, Co represents the element ratio of Co determined from the peak area of Co2p3, and Mn represents the element ratio of Mn determined from the peak area of Mn2p3.
[0045] <Film thickness measurement> T in the above formula (1) can be measured by the following procedure. A sample is prepared by embedding composite particles in a resin material. A cross-section of the sample is processed by an ion milling device. For example, an ion milling device manufactured by Hitachi High-Technologies Corporation, product name IM4000PLUS (or an equivalent product) may be used. The cross-section of the sample is observed by SEM. For example, an SEM device manufactured by Hitachi High-Technologies Corporation, product name Regulus8100 (or an equivalent product) may be used. For 10 composite particles, the film thickness is measured in 5 fields of view. The arithmetic average of the film thicknesses at a total of 50 points is regarded as the film thickness.
[0046] 《ICP measurement》 (Composition ratio of positive electrode active material particles) The composition ratio of the positive electrode active material particles can be measured by the following procedure. A standard solution is prepared by diluting 0.01 g of the positive electrode active material particles with pure water. An ICP-AES device is prepared. For example, an ICP-AES device manufactured by Shimadzu Corporation, product name ICPE-9000 (or an equivalent product) may be used. The emission intensity of the standard solution is measured by the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The molar fraction of the elements contained in the positive electrode active material particles is determined from the emission intensity of the sample solution and the calibration curve.
[0047] (P adhesion amount) Mass fraction of P contained in the composite particle (X P ) can be measured by the following procedure. A mixed acid is prepared by mixing hydrochloric acid, nitric acid, and sulfuric acid. The mixing ratio is "hydrochloric acid / nitric acid / sulfuric acid = 2 / 3 / 1 (molar ratio)". A solution is prepared by dissolving the composite particles in the mixed acid. A sample solution is prepared by diluting 0.01 g of the solution to 100 mL with pure water. Aqueous solutions of P (1000 ppm, 10000 ppm) are prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES device is prepared. The emission intensity of the standard solution is measured using the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The mass fraction (X) of P contained in the composite particles is calculated from the emission intensity of the sample solution and the calibration curve. P) is obtained. Since there is a high possibility that the positive electrode active material particles contain no P or that even if they do contain P, the amount is very small, the mass fraction of P contained in the composite particles (X P ) is considered to be the mass fraction of P contained in the coating film.
[0048] (Mass concentration of Li, P, and Na in the coating solution) The mass concentrations of Li, P, and Na in the coating liquid are measured in the following procedure. 100 ml of sample liquid is prepared by diluting 0.01 g of the coating liquid with pure water. Aqueous solutions of Li, P, and Na (1000 ppm, 10000 ppm) are prepared. A standard solution is prepared by diluting 0.01 g of the aqueous solution with pure water. An ICP-AES device is prepared. The emission intensity of the standard solution is measured using the ICP-AES device. A calibration curve is created from the emission intensity of the standard solution. The emission intensity of the sample liquid (diluted solution of the coating liquid) is measured using the ICP-AES device. The mass concentrations of Li, P, and Na in the coating liquid are determined from the emission intensity of the sample liquid and the calibration curve. The mass concentrations of Li and P are then converted to molar concentrations. The molar concentration of Li (n Li ) is the molar concentration of P (n P ) to obtain the molar ratio (n Li / n P ) is obtained.
[0049] <Composite particles> FIG. 1 is a conceptual diagram showing a composite particle in this embodiment. The composite particle 5 may be called, for example, a "coated positive electrode active material". The composite particle 5 includes a positive electrode active material particle 1 and a coating film 2. The composite particle 5 may form, for example, an aggregate. That is, one composite particle 5 may include two or more positive electrode active material particles 1. The composite particle 5 may have, for example, a D50 of 1 to 50 μm, a D50 of 1 to 20 μm, or a D50 of 5 to 15 μm.
[0050] The coating film 2 is a shell of the composite particle 5. The coating film 2 covers at least a part of the surface of the positive electrode active material particle 1. The coating film 2 contains a phosphate compound. By containing the phosphate compound in the coating film 2, it is expected that heat generation can be suppressed. The coating film 2 may contain, for example, Li, carbon (C), etc.
[0051] The coating film 2 contains, in mass fraction, 0.2 to 10% P. Heat generation can be suppressed by the coating film 2 containing, in mass fraction, 0.2 to 10% P. The coating film 2 preferably contains, in mass fraction, 0.5 to 2.0% P.
[0052] In the composite particle 5, the composition ratio of the particle surface (C Li / C P The composition ratio (C) is 3.5 or less, and preferably 2.5 or less (see formula (2) above). Li / C P By making the composition ratio (C) 2.5 or less, heat generation can be further suppressed. Li / C P ) may be, for example, 1.96 or less, 1.73 or less, or 1.64 or less. Li / C P ) may be zero. Li / C P ) may be, for example, 0.1 or more, 0.5 or more, or 1.0 or more. Li / C P ) may be, for example, 1.64 to 3.1.
[0053] The coverage may be, for example, 80% or more. When the coverage is 80% or more, it is expected that heat generation will be suppressed. The coverage may be, for example, 82% or more, 84% or more, 85% or more, or 88% or more. The coverage may be, for example, 100%, 99% or less, or 95% or less. The coverage may be, for example, 80 to 88%.
[0054] The coating film 2 has a thickness of 1 to 100 nm. When the coating film 2 has a thickness of 1 to 100 nm, the resistance can be suppressed while the coating film 2 functions as a coating. The coating film 2 preferably has a thickness of 5 to 25 nm.
[0055] The positive electrode active material particle 1 is a core of the composite particle 5. The positive electrode active material particle 1 may be a secondary particle (aggregation of primary particles). The positive electrode active material particle 1 (secondary particle) may have a D50 of, for example, 1 to 50 μm, may have a D50 of 1 to 20 μm, or may have a D50 of 3 to 15 μm. If the particle diameter of the positive electrode active material particle 1 is large (for example, more than 50 μm), there is a risk of an increase in resistance.
[0056] The positive electrode active material particles 1 may contain any component. The positive electrode active material particles 1 contain a lithium-containing composite oxide having a layered rock salt structure. The lithium-containing composite oxide is represented by, for example, the following formula (5).
[0057] Li a MO2(5) In the above formula (5), M includes at least one selected from the group consisting of Ni, Co, Mn, and Al, and a may satisfy the relationship of, for example, 0.90≦a≦1.20. The lithium-containing composite oxide may be, for example, Li 1.10 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Li 1.10 Ni 0.50 Co 0.20 Mn 0.30 O2, Li 1.10 Ni 0.60 Co 0.20 Mn 0.20 O2, Li 1.10 Ni 0.80 Co 0.10 Mn 0.10 It may be O2 or the like.
[0058] The positive electrode active material particles 1 contain no P, or if present, only a very small amount.
[0059] <All-solid-state battery> 2 is a conceptual diagram showing an all-solid-state battery in this embodiment. The all-solid-state battery 100 may include, for example, an exterior body (not shown). The exterior body may be, for example, a pouch made of an aluminum laminate film. The exterior body may house a power generating element 50. The power generating element 50 includes a positive electrode 10, a separator layer 30, and a negative electrode 20. That is, the all-solid-state battery 100 includes a positive electrode 10, a separator layer 30, and a negative electrode 20.
[0060] 《Positive electrode》 The positive electrode 10 is layered. The positive electrode 10 may include, for example, a positive electrode active material layer and a positive electrode current collector. For example, the positive electrode active material layer may be formed by applying a positive electrode mixture to the surface of the positive electrode current collector. The positive electrode current collector may include, for example, aluminum (Al) foil or the like. The positive electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0061] The positive electrode active material layer may have a thickness of, for example, 10 to 200 μm. The positive electrode active material layer is in close contact with the separator layer 30. The positive electrode active material layer includes a positive electrode mixture. The positive electrode mixture includes composite particles and a sulfide solid electrolyte. That is, the positive electrode 10 includes composite particles and a sulfide solid electrolyte. Details of the composite particles are as described above.
[0062] The sulfide solid electrolyte can form an ion conduction path in the positive electrode active material layer. The amount of the sulfide solid electrolyte may be, for example, 1 to 200 parts by volume, 50 to 150 parts by volume, or 50 to 100 parts by volume, with respect to 100 parts by volume of the composite particles (positive electrode active material). The sulfide solid electrolyte includes, for example, Li, P, and sulfur (S). The sulfide solid electrolyte may further include, for example, O, silicon (Si), or the like. The sulfide solid electrolyte may further include, for example, a halogen, or the like. The sulfide solid electrolyte may further include, for example, iodine (I), bromine (Br), or the like. The sulfide solid electrolyte may be, for example, glass ceramics or argyrodite. The sulfide solid electrolyte may include, for example, at least one selected from the group consisting of LiI-LiBr-Li3PS4, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2O-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, and Li3PS4.
[0063] The positive electrode active material layer may further include, for example, a conductive material. The conductive material may form an electronic conduction path in the positive electrode active material layer. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The conductive material may include any component. The conductive material may include, for example, at least one selected from the group consisting of carbon black, vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake.
[0064] The positive electrode active material layer may further include, for example, a binder. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the composite particles (positive electrode active material). The binder may include any component. The binder may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene butadiene rubber (SBR), and polytetrafluoroethylene (PTFE).
[0065] 《Negative electrode》 The negative electrode 20 is a counter electrode of the positive electrode 10. The negative electrode 20 is layered. The negative electrode 20 may include, for example, a negative electrode active material layer and a negative electrode current collector. For example, the negative electrode active material layer may be formed by applying a negative electrode mixture to the surface of the negative electrode current collector. The negative electrode current collector may include, for example, a copper (Cu) foil, a Ni foil, or the like. The negative electrode current collector may have a thickness of, for example, 5 to 50 μm.
[0066] The negative electrode active material layer may have a thickness of, for example, 10 to 200 μm. The negative electrode active material layer is in close contact with the separator layer 30. The negative electrode active material layer includes a negative electrode mixture. The negative electrode mixture includes negative electrode active material particles and a sulfide solid electrolyte. The negative electrode mixture may further include a conductive material and a binder. The sulfide solid electrolyte may be the same or different between the negative electrode mixture and the positive electrode mixture. The negative electrode active material particles may include any component. The negative electrode active material particles may include, for example, graphite, Si, silicon oxide [SiO x (0 <x<2)〕、およびLi4Ti5O 12 may contain at least one selected from the group consisting of:
[0067] <Separator layer> The separator layer 30 is interposed between the positive electrode 10 and the negative electrode 20. The separator layer 30 separates the positive electrode 10 from the negative electrode 20. The separator layer 30 includes a sulfide solid electrolyte. The separator layer 30 may further include a binder. The sulfide solid electrolyte may be the same or different between the separator layer 30 and the positive electrode composite. The sulfide solid electrolyte may be the same or different between the separator layer 30 and the negative electrode composite.
[0068] <Method of manufacturing composite particles> 3 is a schematic flow chart of the method for producing composite particles in this embodiment. Hereinafter, the "method for producing composite particles in this embodiment" may be abbreviated as "this production method". This production method includes "(a) preparation of a mixture" and "(b) production of composite particles". This production method may further include, for example, "(c) heat treatment" or the like.
[0069] (a) Preparation of the mixture The present manufacturing method includes preparing a mixture by mixing a coating liquid with positive electrode active material particles. The details of the positive electrode active material particles are as described above. The mixture may be, for example, a suspension or a wet powder. For example, a suspension may be formed by dispersing positive electrode active material particles (powder) in a coating liquid. For example, a wet powder may be formed by spraying a coating liquid into a powder. In the present manufacturing method, any mixing device, granulating device, etc. may be used.
[0070] The coating liquid contains a solute and a solvent. The solute contains a film material (raw material of the coating film). The coating liquid may further contain, for example, a suspended solid (insoluble component), a precipitate, and the like.
[0071] The amount of the solute may be, for example, 0.1 to 20 parts by mass, 1 to 15 parts by mass, or 5 to 10 parts by mass, relative to 100 parts by mass of the solvent. The solvent may contain any component as long as the solute dissolves therein. The solvent may contain, for example, water, alcohol, etc. The solvent may contain, for example, ion-exchanged water, etc.
[0072] The solute may include, for example, a phosphoric acid compound. Thus, the solute may include P. The phosphoric acid compound may include, for example, phosphoric anhydride (P2O5), orthophosphoric acid, pyrophosphoric acid, metaphosphoric acid [(HPO3) n] and polyphosphoric acid. The phosphate compound may be, for example, at least one selected from the group consisting of metaphosphoric acid and polyphosphoric acid. Metaphosphoric acid and polyphosphoric acid may have a longer molecular chain than other phosphate compounds. It is considered that the phosphate compound has a long molecular chain, which makes it easier to generate a coating film having continuity. The coating film having continuity is expected to, for example, improve the coverage rate.
[0073] The solute may further contain sodium (Na). When Na is dissolved in the coating liquid, the stability of the phosphate compound may be improved. The concentration (mass concentration) of Na in the coating liquid may be, for example, 0 to 1%. The concentration of Na may be, for example, 0.6% or less, or 0.5% or less. The concentration of Na may be, for example, 0.5 to 0.6%.
[0074] The solute may further include a lithium compound. The solute may include, for example, lithium hydroxide, lithium carbonate, lithium nitrate, etc. The molar ratio of Li to P (n Li / n P ) may be, for example, 1.5 or less (see formula (3) above). Li / n P ) is 1.5 or less, so that the composition ratio (C Li / C P ) is expected to decrease. Li / n P ) may be, for example, 0.75 or less, 0.30 or less, or zero. Li / n P ) may be, for example, 0 to 0.30 or 0.30 to 1.5.
[0075] (b) Production of Composite Particles The present manufacturing method includes producing composite particles by drying the mixture. The coating liquid attached to the surface of the positive electrode active material particles is dried to produce a coating film. In the present manufacturing method, any drying method can be used.
[0076] For example, the composite particles may be formed by a spray-drying method. That is, the suspension is sprayed from a nozzle to form droplets. The droplets contain the positive electrode active material particles and the coating liquid. For example, the droplets are dried by hot air to form the composite particles. The use of the spray-drying method is expected to improve, for example, the coverage rate.
[0077] The solid content of the suspension for spray drying may be, for example, 1 to 50% or 10 to 30% by volume. The nozzle diameter may be, for example, 0.1 to 10 mm or 0.1 to 1 mm. The hot air temperature may be, for example, 100 to 200°C.
[0078] For example, the composite particles may be produced by a tumbling fluidized bed coating apparatus. In the tumbling fluidized bed coating apparatus, "(a) preparation of the mixture" and "(b) production of the composite particles" can be carried out simultaneously.
[0079] (c) Heat Treatment The present manufacturing method may include subjecting the composite particles to a heat treatment. The coating film may be fixed by the heat treatment. The heat treatment may also be called "baking". In the present manufacturing method, any heat treatment device may be used. The heat treatment temperature may be, for example, 150 to 300°C. The heat treatment time may be, for example, 1 to 10 hours. For example, the heat treatment may be performed in air or in an inert atmosphere. EXAMPLES
[0080] The present embodiment will be described below using examples, but the present embodiment is not limited to these.
[0081] <Production of Positive Electrode Active Material Particles> Positive electrode active material particles A to C, which are lithium-containing composite oxides having a layered rock salt structure, were produced as follows.
[0082] 《Cathode active material particles A》 Nickel(II) sulfate hexahydrate (NiSO4·6H2O), cobalt(II) sulfate heptahydrate (CoSO4·7H2O), and manganese(II) sulfate pentahydrate (MnSO4·5H2O) were dissolved in pure water to obtain a raw solution. The molar ratio of Ni, Co, and Mn in the raw solution was 1:1:1, and the total molar concentration of Ni, Co, and Mn in the raw solution was 1.8 mol / L.
[0083] 1 L of 10 g / L ammonia aqueous solution was prepared in a reaction vessel. 1 L of raw material aqueous solution was dropped into the reaction vessel at a rate of 5.2 mL / min, while adjusting the pH to within 11.20±0.2 using sodium hydroxide aqueous solution to form a precipitate, thereby obtaining a precursor. From the start to the end of the precipitation reaction, the ammonia aqueous solution was appropriately added so that the ammonia concentration of the reaction solution was 10 g / L.
[0084] The precursor was mixed with lithium carbonate (Li2CO3) so that the molar ratio of Li to Ni, Co, and Mn was 1.10, and the mixture was baked at 800°C for 5 hours in an oxygen atmosphere to obtain positive electrode active material particles A. The composition and D50 of the positive electrode active material particles A were measured by the above-mentioned procedure. The composition of the positive electrode active material particles A was Li 1.10 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and D50 was 5.0 μm.
[0085] 《Cathode active material particles B~C》 Positive electrode active material particles B were obtained in the same manner as positive electrode active material particles A, except that the precipitation time was adjusted to obtain a precursor having a D50 of 3.0 μm. Positive electrode active material particles C were obtained in the same manner as positive electrode active material particles A, except that the precipitation time was adjusted to obtain a precursor having a D50 of 20.0 μm. The compositions of positive electrode active material particles B to C were measured by the above-mentioned procedure. The compositions of positive electrode active material particles B to C were Li 1.10 Ni 1 / 3 Co 1 / 3 Mn 1 / 3 It was O2.
[0086] <Manufacturing of all-solid-state batteries> Composite particles, positive electrodes, and all-solid-state batteries according to Nos. 1 to 7 were produced as follows. Hereinafter, for example, "composite particles according to No. 1" may be abbreviated as "No. 1."
[0087] No.1 (Coating liquid) A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate (LiOH HO) was dissolved in the coating solution so that the refractive index was 0.75.
[0088] (positive electrode) Positive electrode active material particles A were prepared. 50 parts by mass of the positive electrode active material particles powder were dispersed in 53.7 parts by mass of the coating liquid to prepare a suspension. A spray dryer manufactured by BUCHI (product name: Mini Spray Dryer B-290) was prepared. The suspension was supplied to the spray dryer to produce a powder of composite particles. The supply air temperature of the spray dryer was 200°C, and the supply air volume was 0.45 m 3 The composite particles were heat-treated in air. The heat treatment temperature was 200°C. The heat treatment time was 5 hours. By the above procedure, the composition ratio (C Li / C P ), mass fraction of P (X P), the thickness (T) and coverage of the coating were measured. P From T, X P The results are shown in Table 1 below. In addition, the composition ratio (C Li / C P ), mass fraction of P (X P ), the thickness (T) and coverage of the coating film shall be measured.
[0089] The following materials were prepared:
[0090] Sulfide solid electrolyte: Li2S-P2S5-based glass ceramics containing LiI (D50: 0.8 μm) Conductive material: VGCF Binder: SBR Dispersion medium: heptane Positive electrode current collector: Aluminum foil The composite particles and the sulfide solid electrolyte were prepared. The composite particles and the sulfide solid electrolyte were weighed in a glove box (dew point: -30°C) filled with argon (Ar) gas. The composite particles and the sulfide solid electrolyte were mixed with a conductive material, a binder, and a dispersion medium to prepare a positive electrode slurry. The mixture ratio was "composite particles / sulfide solid electrolyte = 6 / 4 (volume ratio)". The amount of the conductive material was 3 parts by mass for 100 parts by mass of the composite particles. The amount of the binder was 0.7 parts by mass for 100 parts by mass of the composite particles. The positive electrode slurry was sufficiently stirred by an ultrasonic homogenizer "Model UH-50" manufactured by SMT Corporation. The positive electrode slurry was applied to the surface of the positive electrode current collector to form a coating film. The coating film was dried at 100°C for 30 minutes by a hot plate. In this way, a positive electrode raw sheet was manufactured. A disk-shaped positive electrode was cut out from the positive electrode raw sheet. The area of the positive electrode is 1 cm 2 It was.
[0091] (Negative electrode) The same materials as those for the positive electrode were prepared as the sulfide solid electrolyte, conductive material, binder, and dispersion medium. A Primix Corporation mixer (product name: Filmix, model: 30-L) was prepared as the mixer. The sulfide solid electrolyte, conductive material, binder, and dispersion medium were placed in the mixing vessel of the mixer. The materials in the mixing vessel were mixed at a rotation speed of 20,000 rpm for 30 minutes.
[0092] Li4Ti5O as negative electrode active material particles 12 (D50: 1.0 μm), and Cu foil was prepared as a negative electrode current collector. Negative electrode active material particles were added to the stirring vessel. Stirring was performed at 15000 rpm for 60 minutes. The mixture ratio of the negative electrode active material particles and the sulfide solid electrolyte was "composite particles / sulfide solid electrolyte = 7 / 3 (volume ratio)". The amount of the conductive material was 1 part by mass for 100 parts by mass of the composite particles. The amount of the binder was 2 parts by mass for 100 parts by mass of the composite particles. After the negative electrode active material particles were added, the materials in the stirring vessel were stirred at a rotation speed of 15000 rpm for 60 minutes to prepare a negative electrode slurry. The negative electrode slurry was applied to the surface of the negative electrode current collector to form a coating film. The coating film was dried at 100 ° C. for 30 minutes by a hot plate. In this way, a negative electrode raw material was manufactured. A disk-shaped negative electrode was cut out from the negative electrode raw material. The area of the negative electrode is 1 cm 2 It was.
[0093] (Separator layer) A Li2S-P2S5-based glass ceramic containing LiI (D50: 2.5 μm) was prepared as a sulfide solid electrolyte. 2 A cylindrical ceramic of 64.8 mg was placed in a mold, smoothed, and then subjected to a pressure of 1 ton / cm. 2 The separator layer was obtained by pressing and compacting the mixture at a pressure of 1000 MPa.
[0094] (All-solid-state battery) In the mold, a positive electrode was placed on one side of the separator layer, and a negative electrode was placed on the other side. 2The negative electrode, separator layer, and positive electrode were pressed together for one minute with a pressure of 0.5 ton / cm. A stainless steel rod was placed between the positive electrode and the negative electrode, and a pressure of 0.5 ton / cm was applied. 2 A power generating element was formed by binding the battery element with a binder. A pouch made of aluminum laminate film was prepared as a housing. The battery element was sealed in the housing. This resulted in the formation of an all-solid-state battery.
[0095] No.2 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium hydroxide monohydrate was dissolved in the coating solution so that the ratio of the ionic liquid to the total surface area was 0.30. After this, composite particles, a positive electrode, and an all-solid-state battery were fabricated in the same manner as in No. 1.
[0096] No.3 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. No lithium hydroxide monohydrate was added to the coating solution. From this point on, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1.
[0097] No.4 Positive electrode active material particles B were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. No lithium hydroxide monohydrate was added to the coating solution. From this point on, composite particles, positive electrodes, and all-solid-state batteries were manufactured in the same manner as in No. 1.
[0098] No.5 Positive electrode active material particles A were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n PLithium hydroxide monohydrate was dissolved in the coating solution so that the σ-value was 1.50. After this, composite particles, a positive electrode, and an all-solid-state battery were fabricated in the same manner as in No. 1.
[0099] No.6 Positive electrode active material particles C were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate (LiNO3) was dissolved in the coating solution so that the σ was 2.00. From this point on, the composite particles, the positive electrode, and the all-solid-state battery were produced in the same manner as in No. 1.
[0100] No.7 Positive electrode active material particles C were prepared. A coating solution was prepared by dissolving 10.8 parts by mass of metaphosphoric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in 166 parts by mass of ion-exchanged water. Li / n P Lithium nitrate was dissolved in the coating solution so that the ratio of the ionic liquid to the total surface area was 0.30. After this, the composite particles, the positive electrode, and the all-solid-state battery were produced in the same manner as in No. 1.
[0101] <Evaluation> The capacity of the evaluation battery was confirmed by constant current-constant voltage charging and constant current discharging. The charge / discharge time rate was 1 / 3C. "C" is the symbol for the time rate. At a time rate of 1C, the battery's full charge capacity is discharged in 1 hour.
[0102] The SOC (state of charge) of the evaluation battery was adjusted to 100% (voltage: 3.0V) at a time rate of 1 / 3C. After adjusting the SOC, each solid-state battery was disassembled in a glove box (dew point: -70°C) filled with Ar gas, and the positive electrode was recovered. The recovered positive electrode was cut and 3 mg was placed in a pressure-resistant stainless steel container, and the lid was crimped and sealed. The pressure-resistant stainless steel container was removed from the glove box, and the temperature was increased from room temperature to 500°C at a heating rate of 1°C / min under helium (He) gas flow using a differential scanning calorimeter (DSC) (product name: DSC7000X) manufactured by Hitachi High-Technologies Corporation, and the calorific value was measured. The results are shown in Table 1 below.
[0103] [Table 1]
[0104] <Result> The mass fraction of P in the composite particles measured by ICP-AES (X P In Nos. 1 to 5, where the composition ratio (C / T) is 0.04 or more, the calorific value is reduced. Li / C P The heat generation amount is further reduced in Nos. 1 to 4, in which the coverage ratio is 2.5 or less. The coverage ratio of Nos. 1 to 5 is 80% or more, which is considered to contribute to the reduction in the heat generation amount.
[0105] The mass fraction of P in the composite particles measured by ICP-AES (X P In Nos. 6 and 7, where the heat generation ratio (H / T) is less than 0.04, the heat generation amount increases. In addition, the coverage rate of Nos. 6 and 7 is less than 80%, which is thought to affect the increase in the heat generation amount.
[0106] The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are not restrictive. The technical scope of the present disclosure includes all modifications within the meaning and scope equivalent to the description of the claims. For example, it is also intended from the beginning that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Explanation of symbols]
[0107] 1 positive electrode active material particle, 2 coating film, 5 composite particle, 10 positive electrode, 20 negative electrode, 30 separator layer, 50 power generating element, 100 all-solid-state battery.
Claims
1. A composite particle including a positive electrode active material particle and a coating film, the positive electrode active material particles contain a lithium-containing composite oxide having a layered rock salt structure, the coating film covers at least a part of the surface of the positive electrode active material particle, The coating film contains a phosphoric acid compound, The composite particles have the following formula (1): X P / T≧0.04 (1) Fulfilling the relationship, In the above formula (1), X P represents the mass fraction of phosphorus contained in the composite particles measured by high-frequency inductively coupled plasma optical emission spectrometry, T represents the thickness (nm) of the coating film measured by a scanning electron microscope, The composite particles have the following formula (2): 1.0≦C Li / C P ≦2.5 (2) In the above formula (2), C Li represents the elemental concentration of lithium determined from the peak area of the Li1s spectrum measured by X-ray photoelectron spectroscopy; C P represents the elemental concentration of phosphorus determined from the peak area of the P2p spectrum measured by X-ray photoelectron spectroscopy; The composite particles have a coverage of 80% or more, The coverage is measured by X-ray photoelectron spectroscopy; The positive electrode active material particles have a D50 of 1 to 5 μm, The coating film has a thickness of 1 to 100 nm.
2. A positive electrode comprising the composite particle according to claim 1 and a sulfide solid electrolyte.
3. An all-solid-state battery comprising the positive electrode according to claim 2.
Citation Information
Patent Citations
Lithium battery and preparation method thereof
CN112420977A
All-solid battery
JP2010135090A
Manufacturing method of composite cathode active material, manufacturing method of all-solid battery, and composite cathode active material
JP2011238523A
Cathode active substance material, cathode active substance layer, all-solid battery, and method for producing cathode active substance material
JP2012099323A
Positive electrode active material powder and manufacturing method thereof, and all-solid type lithium secondary battery
JP2018206669A